Fattori Metabolici Nella Risposta Renale All'infusione Di Amino Acidi - A. Claris-Appiani; G. Ardissino; A.S. Tirelli; V. Dacco'; S. Testa; C. Corbetta; L. Guidi; E. Moretto; B.M. Assael; F. Sereni (AboutScience Srl, 1999)
Abstract non disponibile